Preparation method of high-strength transparent wood and application of high-strength transparent wood in building photo-thermal management

By combining chemically modified UV absorbers and parabenzoic acid with space-selective delignin treated wood, high-strength transparent wood is permeated with epoxy resin, which solves the shortcomings of existing transparent wood in terms of mechanical properties, optical transparency and thermal conductivity, and achieves high-performance, environmentally friendly and cost-effective material preparation.

CN119795316APending Publication Date: 2025-04-11SHENZHEN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938687.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing transparent wood is difficult to achieve a balance between mechanical properties and optical transparency, has high thermal conductivity, insufficient UV shielding ability, and complex preparation process, and uses harmful chemicals.

Method used

High-strength transparent wood is prepared by combining chemically modified UV absorbers and parabenzoic acid with spatially selective delignin treated wood.

Benefits of technology

It achieves low density, high mechanical properties, low thermal conductivity and good UV barrier capability, and is suitable for construction, optoelectronics and energy fields, reduces production costs and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795316A_ABST
    Figure CN119795316A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-strength transparent wood, which comprises the following steps: chemically modifying an ultraviolet absorbent to enable the ultraviolet absorbent to have carboxyl groups capable of reacting, then grafting the ultraviolet absorbent and p-hydroxybenzoic acid into the wood subjected to spatial selective delignification, and introducing active groups such as a benzene ring structure and hydroxyl groups into the wood, so that the high-strength transparent wood is obtained. Then epoxy resin is used for permeation, so that the wood has high light transmittance (80%) and high optical haze (93%), light rays can be scattered while the wood is light-transmitting, and glare is reduced; meanwhile, active groups such as hydroxyl in the wood can be combined with the epoxy resin and cured under the action of the hardening agent, so that the wood has good mechanical properties, the mechanical properties of the wood are further enhanced through the benzene ring structure, and the wood has high longitudinal tensile strength (91.95 MPa) and toughness (2.73 MJ m <-3 >) under multiple actions; and therefore, the steel plate can bear larger mechanical load in building application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of transparent wood, and mainly to a preparation method of high-strength transparent wood and application of the high-strength transparent wood in building light and heat management. Background Art

[0002] As global energy consumption continues to grow and environmental problems become increasingly severe, the construction industry, as one of the main areas of energy consumption and carbon emissions, is particularly important for energy-saving and environmentally friendly transformation and upgrading. Building light and heat management, as a key technology to improve energy efficiency and reduce energy consumption, is gradually becoming a research hotspot in the field of building energy conservation. In this context, the development of new green building materials, especially those that can effectively manage light and heat, is of great significance for achieving building energy conservation and improving living comfort. Traditional building materials such as glass and plastics perform well in terms of light transmittance, but have limitations in thermal insulation and mechanical strength. For example, the high thermal conductivity of ordinary glass leads to serious indoor heat loss, which increases the energy consumption of buildings. In addition, the brittleness of glass limits its use in certain applications. Therefore, the development of a building material that is both highly light-transmitting and well-insulated, as well as having high strength, is of great significance for improving building energy efficiency and living comfort.

[0003] Transparent wood, as an emerging sustainable material, has attracted widespread attention due to its excellent optical properties, good mechanical strength, and renewable and biodegradable properties. Through special processing technology, transparent wood not only retains the natural beauty of wood, but also gives it optical transparency, making it show great application potential in the field of building light and heat management. However, the existing transparent wood preparation technology has some limitations:

[0004] First, existing transparent wood often finds it difficult to achieve an ideal balance between mechanical properties and optical transparency, and has a high thermal conductivity, which limits its use in high-performance applications. In addition, due to the low mesopore volume of the wood cell wall, the penetration of the polymer resin is insufficient, affecting the optical transparency of the final product. In addition, the optical transparency of existing transparent wood tends to decrease significantly when the thickness increases, which limits its use in applications that require thicker materials, such as building windows and solar panels. Secondly, existing transparent wood often has insufficient UV shielding capabilities, which may cause UV damage to people and objects indoors, thereby limiting its scope of application. In addition, traditional preparation methods usually involve complex chemical treatment processes, such as delignification using harmful chemicals, which not only burdens the environment but also increases production costs.

[0005] In summary, it is necessary to develop a new technical solution to solve the defects and shortcomings in the existing technology. Summary of the invention

[0006] The purpose of the present invention is to provide a scalable method for preparing high-strength transparent wood for building light and heat management, which can combine the natural texture of wood with excellent optical, thermal and mechanical properties to achieve large-scale production of high-performance transparent wood. The present invention is prepared by combining chemically modified ultraviolet absorbers and p-hydroxybenzoic acid with wood treated with spatially selective delignification, and then infiltrating with epoxy resin. It has the characteristics of low density, high mechanical properties, low thermal conductivity, etc., and is suitable for the fields of construction, optoelectronics and energy.

[0007] An object of the present invention is to provide a method for preparing high-strength transparent wood, comprising the following steps:

[0008] S1, mixing 2,4-dihydroxybenzophenone and triethylamine, then adding acryloyl chloride solution, and reacting under low temperature conditions to obtain compound 1;

[0009] S2, blending the compound 1 with acrylic acid, adding an initiator, and heating for reaction to obtain a compound 2;

[0010] S3, soaking the wood in an acidic sodium chloride (NaClO2) solution, adjusting the pH and performing delignification treatment to obtain delignified wood;

[0011] S4, soaking the delignified wood in a phosphate buffer, adding 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) and NaClO2, then adding NaClO, heating for reaction, washing, and soaking in an AlCl3 solution for ion crosslinking to obtain TEMPO oxidized wood;

[0012] S5, mixing the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2, and heating them for reaction to obtain an intermediate product;

[0013] S6. Immersing the intermediate product in a blend of epoxy resin and hardener, allowing the resin to penetrate the cell wall of the wood, and then curing the wood to obtain high-strength transparent wood.

[0014] Furthermore, in step S1, the mass ratio of 2,4-dihydroxybenzophenone, triethylamine and acryloyl chloride is 1:(0.3-1.5):(0.1-1).

[0015] Furthermore, in step S1, the low temperature is 0-10°C.

[0016] Furthermore, in step S2, the mass ratio of the compound 1 to acrylic acid is 1:(1-3).

[0017] Furthermore, in step S2, the heating temperature is 60-75°C.

[0018] Furthermore, in step S3, the pH is 4-6.

[0019] Furthermore, in step S4, the mass ratio of the delignified wood, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, NaClO2 and NaClO is 1:(0.01-0.05):(1-3):(0.1-0.5).

[0020] Furthermore, in step S4, the heating temperature is 50-70°C.

[0021] Furthermore, in step S5, the mass ratio of the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2 is (5-20):(0.5-2):(0.5-2).

[0022] Furthermore, in step S5, the heating temperature is 60-80°C.

[0023] Further, step S3 selection and pretreatment of wood raw materials: Select suitable wood raw materials and perform delignification treatment to retain the cell wall structure of the wood and remove part of the lignin component. This step is critical because it determines the optical and mechanical properties of the final product. Delignification treatment can be performed by acidic sodium chloride solution at a specific pH value and temperature to ensure effective removal of lignin without damaging the structure of cellulose.

[0024] Furthermore, the wood raw material is preferably fir wood, because it has a clear contrast between early wood and late wood structures and is suitable for preparing transparent wood with natural patterns.

[0025] Further, the delignification treatment should ensure that the lignin in the early wood (EW) region is effectively removed, while the late wood (LW) region retains some lignin to maintain the natural pattern. The treated wood is washed with water to remove residual chemicals.

[0026] Furthermore, step S4 spatially selective delignification treatment: a TEMPO-mediated oxidation method is used to perform spatially selective delignification treatment on the wood to increase the mesoporous volume and specific surface area of ​​the wood cell wall, thereby improving its adsorption capacity for the polymer resin. This treatment step enhances the interaction between the wood and the resin by introducing functional groups such as carboxyl and hydroxyl groups into the wood cell wall, thereby improving the overall performance of the composite material.

[0027] Furthermore, step S6 epoxy resin penetration and curing: at room temperature, the wood that has been subjected to spatially selective delignification treatment and modification is immersed in epoxy resin for solvent-free penetration to ensure that the resin completely penetrates the wood cell wall and achieves uniform distribution of the resin in the wood cell wall. This step is carried out at room temperature, and then, through curing treatment, the infiltrated wood and the resin form high-performance transparent wood.

[0028] Another object of the present invention is to provide an application of the high-strength transparent wood prepared by the above-mentioned preparation method of the high-strength transparent wood in building light and heat management.

[0029] In the application of building light and heat management, the high-strength transparent wood of the present invention can be widely used in glass ceilings, roofs, transparent decorations and indoor partitions, etc., which can not only provide comfortable indoor lighting, but also effectively reduce indoor energy consumption. For example, the high optical transmittance and high optical haze of transparent wood enable it to scatter light while transmitting light, reduce glare, and improve indoor light comfort. In addition, its low thermal conductivity helps to reduce heat transfer and improve the thermal insulation performance of buildings. Therefore, the high-strength transparent wood of the present invention has broad application prospects in the field of building light and heat management, and helps to promote the green and sustainable development of the construction industry. In summary, the high-strength transparent wood of the present invention not only has significant advantages in optical properties, mechanical properties and thermal insulation properties, but also performs well in environmental friendliness and cost-effectiveness, providing a new material choice for building light and heat management. With the continuous development of transparent wood technology and the continuous expansion of its application fields, its application prospects in the future construction and optoelectronic fields will be broader, making important contributions to achieving sustainable development goals.

[0030] The present invention has the following beneficial effects:

[0031] (1) The present invention chemically modifies the ultraviolet absorber to make it have a reactive carboxyl group, and then grafts it with p-hydroxybenzoic acid into the wood that has undergone spatial selective delignification, introduces a benzene ring structure and active groups such as hydroxyl groups into the wood, and then uses epoxy resin to infiltrate and cure, thereby preparing high-strength transparent wood. Since the wood that has undergone spatial selective delignification has a high mesoporous area and specific surface area, after solvent-free infiltration of epoxy resin, the epoxy resin can fully enter the cell wall of the wood, and the resin is evenly distributed in the cell wall of the wood. The prepared wood has a high light transmittance (80%) and a high optical haze (93%), so that it can scatter light while transmitting light, reduce glare, and improve indoor light comfort; at the same time, the active groups such as hydroxyl groups in the wood can combine with the epoxy resin, so that the cured wood has good mechanical properties, and the benzene ring structure further enhances the mechanical properties of the wood. Under various effects, the wood has high longitudinal tensile strength (91.95MPa) and toughness (2.73MJ m -3), which enables it to withstand greater mechanical loads such as wind pressure and snow pressure in building applications, while its low thermal conductivity (0.42W m -1 K -1 ) also helps to reduce heat transfer, improve the thermal insulation performance of the building, and help improve the energy efficiency of the building, thereby reducing energy consumption. In addition, the ultraviolet absorber of the present invention can be tightly combined with the wood through chemical bonds, so that the wood has good ultraviolet radiation resistance, and the ultraviolet transmittance is only 15%, which helps to protect indoor people and objects from ultraviolet damage.

[0032] (2) The simplified preparation process and use of environmentally friendly materials in the present invention help reduce production costs and demonstrate good large-scale production capabilities. The maximum preparation size can reach 320 mm × 170 mm × 0.6 mm. At a higher thickness, it still maintains good optical transparency, with a maximum transmittance of 80%, which indicates its great practical application potential.

[0033] (3) The preparation method of the present invention reduces the use of harmful chemicals and meets the requirements of sustainable development. At the same time, the prepared transparent wood is biodegradable, reducing the problem of waste disposal.

[0034] (4) High transparency and retention of natural patterns: Through spatially selective delignification treatment, not only the optical transparency of the wood is improved, but also the natural growth ring pattern of the wood is successfully retained, increasing its aesthetics.

[0035] (5) Scalability: The method of the present invention has good scalability potential and is suitable for large-scale production, which will help promote the widespread application of transparent wood in the market. By optimizing the parameters of each step, such as the conditions of delignification treatment, the intensity of TEMPO-mediated oxidation treatment, the temperature and time of evaporative drying, the concentration and time of ionic crosslinking, the process of resin penetration and curing, etc., high-efficiency and low-cost production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Raw Douglas fir wood texture detail shown.

[0037] Figure 2 The natural texture of Douglas fir wood after TEMPO oxidation treatment in Example 1 is shown.

[0038] Figure 3 The transparency and haze of Example 1 and Comparative Examples 1-3 are shown.

[0039] Figure 4 The thermal conductivities of Example 1 and Comparative Examples 1-2 are shown.

[0040] Figure 5The anti-ultraviolet performance of Example 1 and Comparative Examples 1-3 is shown.

[0041] Figure 6 The mechanical tensile curves and bending toughness of Example 1 and Comparative Examples 1-3 are shown;

[0042] in,

[0043] Figure 6 (a) shows the mechanical stretching curves of Example 1 and Comparative Examples 1-3;

[0044] Figure 6 (b) shows the bending toughness of Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0045] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0046] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0047] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers indicating, for example, the amounts of ingredients used in the specification and claims should be understood to be modified in all cases by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values ​​that vary depending on the desired properties to be obtained by the present invention.

[0048] The following raw materials are used in the embodiments of the present invention:

[0049] The hardener was polyamide 650, purchased from Jinan Shuangying Chemical.

[0050] Example 1

[0051] A method for preparing high-strength transparent wood comprises the following steps:

[0052] S1. Using tetrahydrofuran as solvent, 2,4-dihydroxybenzophenone and triethylamine were mixed, and then 36% v / v acryloyl chloride tetrahydrofuran solution (2,4-dihydroxybenzophenone: triethylamine: acryloyl chloride = 1:0.5:0.8, m / m / m) was added, and the mixture was reacted at 4°C for 10 h. The mixture was centrifuged, and the supernatant was added to a saturated sodium bicarbonate solution. The solid was filtered, washed, and dried to obtain compound 1.

[0053] S2, using water as solvent, mixing the compound 1 with acrylic acid (compound 1: acrylic acid = 1:1, m / m), adding 1% sodium persulfate by mass of the reactants, reacting at 70° C. for 8 h, washing, and drying to obtain compound 2;

[0054] S3, cutting Douglas fir into a size of 320 mm × 170 mm × 0.6 mm, soaking in a 1 wt% NaClO2 solution, adjusting the pH to 4.6 with glacial acetic acid, and performing delignification treatment for 2 h, then washing with deionized water for 3 times, and drying to obtain delignified wood;

[0055] S4, soaking 1 g of the delignified wood in 100 ml of sodium phosphate buffer (pH 6.8), adding 0.032 g of TEMPO and 2.26 g of NaClO2, then adding 20 mL of 0.1 M NaClO solution, reacting at 60° C. for 2 h, then washing with deionized water, and soaking in 0.1 M AlCl3 solution for 1 h, then soaking in 0.01 M AlCl3 solution for 24 h for ion crosslinking, washing, and drying to obtain TEMPO-oxidized wood;

[0056] S5, using ethanol as solvent, mixing the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2 (TEMPO-oxidized wood: p-hydroxybenzoic acid: compound 2 = 20:1:1, m / m / m), heating at 70° C. for 10 h, washing and drying to obtain an intermediate product;

[0057] S6. Immerse the intermediate product in a blend of Aero-Marine epoxy resin #300 and hardener (Aero-Marine epoxy resin #300: hardener=10:1, m / m) for 24 hours to allow the resin to penetrate the wood cell wall, and then cure it at room temperature for 24 hours to obtain high-strength transparent wood.

[0058] Figure 1 Showing raw Douglas fir wood texture detail. Figure 1 It can be seen that there is a clear structural contrast between its earlywood (EW) and latewood (LW).

[0059] Figure 2The natural texture of Douglas fir wood after TEMPO oxidation treatment in Example 1 is shown. Figure 2 It can be seen that after TEMPO oxidation treatment of Douglas fir, the lignin in the earlywood area is effectively removed, while some lignin is retained in the latewood area, thus maintaining the natural texture of the wood.

[0060] Example 2

[0061] A method for preparing high-strength transparent wood comprises the following steps:

[0062] S1. Using tetrahydrofuran as solvent, 2,4-dihydroxybenzophenone and triethylamine were mixed, and then 36% v / v acryloyl chloride tetrahydrofuran solution (2,4-dihydroxybenzophenone: triethylamine: acryloyl chloride = 1:0.5:0.8, m / m / m) was added, and the mixture was reacted at 4°C for 10 h. The mixture was centrifuged, and the supernatant was added to a saturated sodium bicarbonate solution. The solid was filtered, washed, and dried to obtain compound 1.

[0063] S2, using water as solvent, mixing the compound 1 with acrylic acid (compound 1: acrylic acid = 1:1, m / m), adding 1% sodium persulfate by mass of the reactants, reacting at 70° C. for 8 h, washing, and drying to obtain compound 2;

[0064] S3, cutting Douglas fir into a size of 320 mm × 170 mm × 0.6 mm, soaking in a 0.5 wt% NaClO2 solution, adjusting the pH to 4.5 with glacial acetic acid, and performing delignification treatment for 3 h, then washing with deionized water for 3 times, and drying to obtain delignified wood;

[0065] S4, soaking 1 g of the delignified wood in 100 ml of sodium phosphate buffer (pH 6.8), adding 0.028 g of TEMPO and 2 g of NaClO2, then adding 30 mL of 0.05 M NaClO solution, reacting at 50° C. for 4 h, then washing with deionized water, and soaking in 0.1 M AlCl3 solution for 1 h, then soaking in 0.01 M AlCl3 solution for 24 h for ion crosslinking, washing, and drying to obtain TEMPO-oxidized wood;

[0066] S5, using ethanol as solvent, mixing the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2 (TEMPO-oxidized wood: p-hydroxybenzoic acid: compound 2 = 20:1:1, m / m / m), heating at 70° C. for 10 h, washing and drying to obtain an intermediate product;

[0067] S6. Immerse the intermediate product in a blend of Aero-Marine epoxy resin #300 and hardener (Aero-Marine epoxy resin #300: hardener=8:1, m / m) for 24 hours to allow the resin to penetrate the wood cell wall, and then cure it at room temperature for 24 hours to obtain high-strength transparent wood.

[0068] Example 3

[0069] A method for preparing high-strength transparent wood comprises the following steps:

[0070] S1. Using tetrahydrofuran as solvent, 2,4-dihydroxybenzophenone and triethylamine were mixed, and then 36% v / v acryloyl chloride tetrahydrofuran solution (2,4-dihydroxybenzophenone: triethylamine: acryloyl chloride = 1:0.5:0.8, m / m / m) was added, and the mixture was reacted at 4°C for 10 h. The mixture was centrifuged, and the supernatant was added to a saturated sodium bicarbonate solution. The solid was filtered, washed, and dried to obtain compound 1.

[0071] S2, using water as solvent, mixing the compound 1 with acrylic acid (compound 1: acrylic acid = 1:1, m / m), adding 1% sodium persulfate by mass of the reactants, reacting at 70° C. for 8 h, washing, and drying to obtain compound 2;

[0072] S3, cutting Douglas fir into a size of 320 mm × 170 mm × 0.6 mm, soaking in a NaClO2 solution with a concentration of 1.5 wt%, adjusting the pH to 4.7 with glacial acetic acid, and performing delignification treatment for 4 hours, then washing with deionized water for 3 times, and drying to obtain delignified wood;

[0073] S4, soaking 1 g of the delignified wood in 100 ml of sodium phosphate buffer (pH 6.8), adding 0.036 g of TEMPO and 3 g of NaClO2, then adding 10 mL of 0.15 M NaClO solution, reacting at 70° C. for 1 h, then washing with deionized water, and soaking in 0.1 M AlCl3 solution for 1 h, then soaking in 0.01 M AlCl3 solution for 24 h for ion crosslinking, washing, and drying to obtain TEMPO-oxidized wood;

[0074] S5, using ethanol as solvent, mixing the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2 (TEMPO-oxidized wood: p-hydroxybenzoic acid: compound 2 = 20:1:1, m / m / m), heating at 70° C. for 10 h, washing and drying to obtain an intermediate product;

[0075] S6. Immerse the intermediate product in a blend of Aero-Marine epoxy resin #21 and hardener (Aero-Marine epoxy resin #21: hardener=7:1, m / m) for 24 hours to allow the resin to penetrate the wood cell wall, and then cure it at room temperature for 24 hours to obtain high-strength transparent wood.

[0076] Comparative Example 1

[0077] A method for preparing high-strength transparent wood. The difference between this comparative example and Example 1 is that step S4 is not performed. In step S3, NaClO2 solution is used for treatment for 10 hours to completely remove lignin. In step S5, the mass of the TEMPO-oxidized wood is replaced with delignified wood. The rest of the preparation method and content are the same as those in Example 1.

[0078] Comparative Example 2

[0079] A method for preparing high-strength transparent wood. The difference between this comparative example and Example 1 is that step S6 is not performed, and the intermediate product is used as the high-strength transparent wood. The rest of the preparation method and content are the same as those in Example 1.

[0080] Comparative Example 3

[0081] This comparative example is untreated Douglas fir.

[0082] Comparative Example 4

[0083] A method for preparing high-strength transparent wood. The difference between this comparative example and Example 1 is that in step S5, the mass of the p-hydroxybenzoic acid is replaced by benzoic acid, and the rest of the preparation method and content are the same as those in Example 1.

[0084] Comparative Example 5

[0085] A method for preparing high-strength transparent wood. The difference between this comparative example and Example 1 is that in step S5, the mass of the compound 2 is replaced by 2,4-dihydroxybenzophenone, and the rest of the preparation method and content are the same as those in Example 1.

[0086] Test Case

[0087] The key performances of Example 1 and Comparisons 1-5 were tested.

[0088] Test method:

[0089] Light transmittance: Refer to GB / T 2679.1-2020 "Determination of transparency of paper - diffuse reflection method".

[0090] Haze: Refer to GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics"

[0091] Tensile strength: refer to GB / T 7991.9-2014 "Test methods for glass-lined layers Part 9: Determination of tensile strength".

[0092] Toughness: Refer to GB / T 1940-2009 "Test method for impact toughness of wood".

[0093] Thermal conductivity: Refer to GB / T 39862-2021 "Test of thermal conductivity of high thermal conductivity ceramics".

[0094] Ultraviolet transmittance: refer to GB / T 2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet transmittance and related window glass parameters of architectural glass".

[0095] The performance test results are shown in Table 1.

[0096] Figure 3 The transparency and haze of Example 1 and Comparative Examples 1-3 are shown.

[0097] Figure 4 The thermal conductivities of Example 1 and Comparative Examples 1-2 are shown.

[0098] Figure 5 The anti-ultraviolet performance of Example 1 and Comparative Examples 1-3 is shown.

[0099] Figure 6 The mechanical tensile curves and bending toughness of Example 1 and Comparative Examples 1-3 are shown;

[0100] in,

[0101] Figure 6 (a) shows the mechanical stretching curves of Example 1 and Comparative Examples 1-3;

[0102] Figure 6 (b) shows the bending toughness of Example 1 and Comparative Examples 1-3.

[0103] Table 1 Performance test results of Example 1 and Comparison 1-5

[0104]

[0105] It can be seen from the above test results that the high-strength transparent wood prepared in Example 1 has a light transmittance of 80% and a haze of 93%. However, due to the complete delignification treatment, the light transmittance of the wood in Comparative Example 1 reaches 87%, but the haze is reduced to 65%, indicating that its scattering ability is reduced; the wood in Comparative Example 2 is not polymer-infiltrated, and its light transmittance and haze are significantly lower than those in Example 1, lower than 60% and 80% respectively, because the pores of the wood cannot effectively scatter light due to the lack of polymer filling; the light transmittance of the wood in Comparative Example 3 is extremely low, less than 10%, and the haze is also low, because the natural cell structure of the wood strongly absorbs and scatters light.

[0106] In terms of ultraviolet transmittance, the high-strength transparent wood prepared in Example 1 has excellent ultraviolet blocking ability due to spatially selective delignification, grafting of ultraviolet absorbers, and then reacting with epoxy resin. Although the wood in Comparative Example 1 still has a certain ultraviolet blocking ability, its absorption performance in the range of 200-400nm is not as good as that in Example 1 due to the complete removal of lignin and the lack of grafting of ultraviolet absorbers; although the wood in Comparative Example 2 retains a certain amount of lignin, its ultraviolet blocking ability is not as good as that in Example 1 due to the lack of polymer protection; the wood in Comparative Example 3 has a certain ultraviolet blocking ability, but due to the lack of treatment, its absorption performance in the range of 200-400nm is not as good as that in Example 1; Comparative Example 5 replaces the modified ultraviolet absorber with an unmodified ultraviolet absorber, and the ultraviolet absorber is difficult to graft onto the wood, so the ultraviolet blocking ability is relatively poor relative to that in Example 1.

[0107] In terms of mechanical properties, the high-strength transparent wood prepared in Example 1 has a longitudinal tensile strength of 91.95 MPa and a mechanical strength of 2.73 MJ m -3 The wood in Comparative Example 1 was completely delignified, which resulted in a decrease in mechanical properties of the wood. In particular, after long-term treatment, the integrity of the wood may not be maintained, resulting in lower tensile strength and toughness of the comparative example than that of Example 1. The wood in Comparative Example 2 was not polymer-infiltrated, and its mechanical properties were significantly lower than those of Example 1, especially the tensile strength and toughness, which were lower than 40 MPa and 0.5 MJ m, respectively. -3 The mechanical properties of the wood in Comparative Example 3 remain in their natural state, but due to the lack of reinforcement treatment, their tensile strength and toughness are lower than 10MPa and 0.2MJ m -3 In Comparative Example 4, since p-hydroxybenzoic acid is replaced by benzoic acid, although it can combine with wood, it cannot react with epoxy resin later, so its mechanical properties are worse than those of Example 1.

[0108] In summary, it can be clearly seen that the steps of spatially selective delignification treatment, grafting of p-hydroxybenzoic acid and UV absorber, and then using polymer infiltration curing in Example 1 are crucial to improving the optical and mechanical properties of wood. These steps not only improve the light transmittance and haze of wood, but also enhance its UV blocking ability and mechanical properties, making it an ideal material for energy-efficient building applications. The comparative example further confirms the necessity of the pretreatment step for obtaining high-performance transparent wood.

[0109] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0110] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing high-strength transparent wood, characterized in that: The steps include: S1, mixing 2,4-dihydroxybenzophenone and triethylamine, then adding acryloyl chloride solution, and reacting under low temperature conditions to obtain compound 1; S2, blending the compound 1 with acrylic acid, adding an initiator, and heating for reaction to obtain a compound 2; S3, soaking the wood in an acidic sodium chloride solution, adjusting the pH and performing delignification treatment to obtain delignified wood; S4, soaking the delignified wood in a phosphate buffer, adding 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and NaClO2, then adding NaClO, heating for reaction, washing, and soaking in an AlCl3 solution for ion crosslinking to obtain TEMPO oxidized wood; S5, mixing the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2, and heating them for reaction to obtain an intermediate product; S6. Immersing the intermediate product in a blend of epoxy resin and hardener, allowing the resin to penetrate the cell wall of the wood, and then curing the wood to obtain high-strength transparent wood.

2. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S1, the mass ratio of 2,4-dihydroxybenzophenone, triethylamine and acryloyl chloride is 1:(0.3-1.5):(0.1-1).

3. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S1, the low temperature is 0-10°C.

4. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S2, the mass ratio of the compound 1 to acrylic acid is 1:(1-3).

5. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S2, the heating temperature is 60-75°C.

6. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S3, the pH is 4-6.

7. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S4, the mass ratio of the delignified wood, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, NaClO2 and NaClO is 1:(0.01-0.05):(1-3):(0.1-0.5).

8. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S4, the heating temperature is 50-70°C.

9. The method for preparing high-strength transparent wood according to claim 1, characterized in that: In step S5, the mass ratio of the TEMPO-oxidized wood, p-hydroxybenzoic acid and compound 2 is (5-20):(0.5-2):(0.5-2).

10. Application of the high-strength transparent wood prepared by the method for preparing the high-strength transparent wood according to any one of claims 1 to 9 in building light and heat management.